Evaluation of Academic Supervision Services of School Supervisors Based on the Satisfaction of Mathematics Teachers Using Technology at Senior High School - Ruslan Ruslan; Iwan Setiawan HR; Alfiah Nurfadhilah AM Hindi (Indonesian Journal of Educational Studies, 2022)
Abstract. This research aims to determine the quality of academic supervision services of school supervisors on the level of satisfaction of mathematics teachers using technology like handphone or laptop in pandemic Covid-19 at Senior High School (SMA) in Bone District and to determine what factors should be prioritized. This research is a descriptive-correlational using the ex post facto survey method, therefore to obtain data on this research variable the researcher does not treat the research sample but only examines the facts that have occurred, have been felt or have been done by the mathematics teacher. This descriptive-correlational research uses the ex post facto survey method, therefore to obtain data on this research variable the researcher does not treat the research sample but only examines the facts that have occurred, have been felt or have been done by the mathematics teacher. The population is SMA Mathematics teachers in Bone district. The sample was taken at random proportional stratified (stratified proportional random sampling) with a Likert model scale questionnaire. Then the respondent's answer was analyzed descriptively and with IPA analysis (Importance-Performance Analysis). The results showed that the teacher's actual satisfaction with the performance of school supervisors was in the aspects of Mathematics Curriculum Development, Mathematics Learning Process aspects, Mathematics Learning Evaluation aspects, and Mathematics Teacher Professionalism Development. Keywords: Qualitiy of Service; Supervision; IPA Analysis; Technology.